Integrated household surveys: An assessment of U.S. methods and an innovation - Krislert Samphantharak; Scott Schuh; Robert M. Townsend (Federal Reserve Bank of Boston, 2017)
We present a vision for improving household financial surveys by integrating responses from questionnaires more completely with financial statements and combining them with payments data from diaries. Integrated household financial accounts - balance sheet, income statement, and statement of cash flows - are used to assess the degree of integration in leading U.S. household surveys, focusing on inconsistencies in measures of the change in cash. Diaries of consumer payment choice can improve dynamic integration. Using payments data, we construct a statement of liquidity flows: a detailed analysis of currency, checking accounts, prepaid cards, credit cards, and other payment instruments, consistent with conventional cash-flows measures and the other financial accounts.
Keywords: D12; D14; E41; E42; 330; Surveys; diaries; payments; financial statements; cash flows